Effect of thermostat position and its set-point temperature on the performance of a domestic electric water heater - Kizilors, Cafer; Aydin, Devrim (Oxford Univ Press, 2020)
In domestic buildings, water is generally heated by an immersion type electric water heater, equipped with a thermostat as one unit, which is fitted at the bottom of the tank. Despite these systems are driven by electric energy, which is not favorable compared to direct solar water heaters, they are still widely used due to the practicality and low installation costs. In current use of electric water heaters, thermostat position and water set-point temperature are crucial and these parameters should be optimized for efficient and economic use of such systems. In this study, the impact of placing the thermostat at three different elevations; namely near the bottom, in the middle and near the top of an EWH is experimentally investigated. In addition, the effect of temperature setting of the thermostat near the bottom of the tank, on the performance of the EWH is experimentally investigated. Data were obtained for 5 L/min discharging rate of the heated water. The discharge efficiencies are found to be higher for the thermostat position at the bottom, while the discharge efficiencies for thermostat positions in the middle and near the top are very close but lower than that of the one near the bottom.
Keywords: electric water heater; heat storage; thermal stratification; thermostat; experimental